2002
DOI: 10.2320/matertrans.43.49
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrochemical Properties of Al-Added Molybdate Conversion Coatings on Zinc

Abstract: Molybdate conversion coatings were deposited on zinc substrate in the presence of Al to improve the corrosion resistance and their structural and electrochemical properties were characterized with various analytical techniques. Infrared reflectance spectroscopy analysis indicated that Al existed as Al(OH) 3 in the molybdate conversion coatings. It was found that the addition of Al to molybdate conversion coatings hindered the oxygen reduction and hydrogen evolution reactions effectively compared with pure moly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…While corrosion inhibitors frequently act by altering the properties of oxide films of metals and alloys, [9][10][11][12][13][14][15][16] work by Clark et al on high strength aluminium alloy 2024-T3 shows that the chromate inhibition mechanism involves chemisorption of Cr(III) at cathodic sites (such as Cu inclusions) which poisons the oxygen reduction reaction. 17 The filaments on the attacked grains propagated in preferential directions that were parallel to the prismatic directions of thev1010w and v1120w families of directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While corrosion inhibitors frequently act by altering the properties of oxide films of metals and alloys, [9][10][11][12][13][14][15][16] work by Clark et al on high strength aluminium alloy 2024-T3 shows that the chromate inhibition mechanism involves chemisorption of Cr(III) at cathodic sites (such as Cu inclusions) which poisons the oxygen reduction reaction. 17 The filaments on the attacked grains propagated in preferential directions that were parallel to the prismatic directions of thev1010w and v1120w families of directions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schmutz et al 5 have investigated the effects of dichromate ions on the corrosion of high purity polycrystalline Mg in Cl 2 containing environments. While corrosion inhibitors frequently act by altering the properties of oxide films of metals and alloys, [9][10][11][12][13][14][15][16] work by Clark et al on high strength aluminium alloy 2024-T3 shows that the chromate inhibition mechanism involves chemisorption of Cr(III) at cathodic sites (such as Cu inclusions) which poisons the oxygen reduction reaction. 17 With respect to Mg, Schmutz et al observed uniform dissolution under open circuit conditions in 0 .…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] In the effort to eliminate the harm of Cr 6+ to the environment, a series of novel CCPs have been carried out at home and abroad. [13][14][15][16][17] However, according to the results of their research, most of the recent CCPs have their own shortcomings, which limit their further application and promotion. [18] As for the reported CCPs, one of the most remarkable processes is cobaltate CCP, and the main reasons are as follows: Co is an essential trace element for the human body and an essential component of vitamin B12; the equilibrium potential of Co 3+ /Co 2+ (+1.82 V) ion pair is higher than that of Cr 6+ /Cr 3+ (+1.56 V), which means that the corrosion resistance of Co conversion coating (CoCC) is better than that of Cr conversion coating (CrCC) from the perspective of thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] In the effort to eliminate the harm of Cr 6+ to the environment, a series of novel CCPs have been carried out at home and abroad. [ 13–17 ] However, according to the results of their research, most of the recent CCPs have their own shortcomings, which limit their further application and promotion. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%